Identifikasi Sistem Manajemen Pendidikan pada Sekolah Menengah Pertama di Kecamatan Pulau Haruku, Kabupaten Maluku Tengah - Sitti Bariah Marasabessy; T.G. Ratumanan; l.J Lokollo; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
One of the factors that supports the achievement of educational goals is educational management in junior high schools. Haruku Island District is one of the Districts in Central Maluku Regency which has 8 junior high schools, both public, private and Tsanawiyah junior high schools. This research aims to identify the educational management system at the junior high school level in Pulau Haruku District, Central Maluku Regency, and identify the factors that influence the educational management system. This research is qualitative research where data collection techniques use observation techniques. Data analysis was carried out using two tools to identify systems, namely Rich Pictures and Fishbone Diagrams